PENDAMPINGAN KEGIATAN PEMBERIAN MAKANAN TAMBAHAN (PMT) PADA ANAK USIA DINI MENGGUNAKAN OLAHAN RUMPUT LAUT DI TK. AISYIYAH BUSTANUL ATHFAL 1 KECAMATAN ASEMBAGUS KABUPATEN SITUBONDO - Ika Junia Ningsih; Ismi Jasila; Abdul Muqsith (LP2M Universitas Ibrahimy, 2022)
Seaweed has the potential to be developed as a food product with high nutritional and economic value. Nori is red seaweed (Porphyra algae) that is mashed until the liquid inside comes out then it is flattened and dried in direct sunlight to dry. Nori has nutritional components that have been studied for health benefits, including 45.2% protein, 40% fiber, 47.31% carbohydrates, 4.99% ash, 0.44% fat, and 13.14% water. It also contains 10 types of amino acids, such as threonine, arginine, tyrosine, methionine, lysine, valine, glutamic acid, glycine, phenylalanine, and alanine which can play a role in optimizing protein needs and increasing community growth, especially growth in early childhood as shoots. nation to improve human resources. The activity of providing supplementary food (PMT) based on nori is carried out on group A kindergarten students Aisyiyah Bustanul Athfal 1 Asembagus was chosen as a community service activity to realize increased nutrition in early childhood through healthy food sources of marine protein. The method used in this activity is Participatory Action Research (PAR) where direct assistance is carried out through active participation in schools. The results of the activity showed that the class A students were able to understand the information conveyed about the activity and had a very good acceptance of the additional food provided.